The Indian Stock Market: A Comparative Study of Mutual Funds & Foreign Institutional Investors - Yadav, J. S.; Yadav, O. S. (Indian Journal of Finance, 2012)
In developing countries like India, there is a great need of investments in the economy. Small savings of individuals should be channelized into capital formulation for the growth of the economy. There are many financial engines like banks, financial institutions, mutual funds, primary capital markets, NBFI, FIIs etc. that are functioning for boosting the economy. Besides banks and financial institutions, MFs and FIIs also have a great impact on the investment in the economy. This present paper is an attempt to compare the participation of mutual funds and Foreign Institutional investors' investments in the Indian economy and their investment performance in equity as well as in debts.